Web-Based Decision Support System for Best Employee Selection in Government Institutions using Analytical Hierarchy Process (AHP) Method - Prapto, Dwi Atmodjo Wismono; Sipahutar, Rosen; Purwaningsih, Mardiana (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Government institutions are often constrained when making decisions regarding selecting the best employees due to the unavailability of an adequate decision support system. In fact, with this system, determining the best employees can be done easily and quickly. One method that can be used is the Analytical Hierarchy Process (AHP) which supports multi-criteria selection. This web-based decision support system designed has six criteria. From the calculation results of the priority weight value for each standard, the Court Punishment criteria have the highest priority value compared to other measures. Thus the requirements for this Court Punishment will be the primary consideration in calculating the value of outstanding employees. These criteria are then used for the simulation of 10 ministry employees. The simulation results show that the designed AHP technique is proven to prepare data for high achieving employee candidates accurately.